THE STEGANOGRAPHIC SYSTEM FOR HIDDEN TRANSFER OF THE COLOR IMAGES - Reznik, I. A.; Sadykhov, R. Kh. (International Journal of Computing, 2014)
In the given work the system of the hidden transfer of the graphic information is considered. For hiding the graphic information the digital correlations based on the complex BIFORE transform are used. A crypto stability of a technique is provided by a secret key, with that the hidden image is embedded in the container-image. The problems of efficiency, robustness, accuracy and performance of the suggested method are considered.